2015
DOI: 10.1111/jonm.12343
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nursing time spent on administration of medication in an Australian residential aged care home

Abstract: Aims: To examine nursing time spent on administration of medications in a residential aged care (RAC) home, and to determine factors that influence the time to medicate a resident. Background: Information on nursing time spent on medication administration is useful for planning and implementation of nursing resources.Methods: Nurses were observed over 12 morning medication rounds using a time-motion observational method and field notes, at two high-care units in an Australian RAC home.Results: Nurses spent bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…Medication management is a significant component of direct care activities in RACFs and reducing time spent administering medications may enable staff to shift a meaningful period of time to other care activities or spend more time on other medication safety initiatives [40]. Previous studies have identified that time spent on medication rounds by nurses varies from approximately 1 h for 20 residents, to 4.5 h for 35 residents [43][44][45]. Data from three RACFs participating in the SIMPLER study suggests nurses spend an average of five minutes administering medications per resident per round [45].…”
Section: Clinical Significancementioning
confidence: 99%
“…Medication management is a significant component of direct care activities in RACFs and reducing time spent administering medications may enable staff to shift a meaningful period of time to other care activities or spend more time on other medication safety initiatives [40]. Previous studies have identified that time spent on medication rounds by nurses varies from approximately 1 h for 20 residents, to 4.5 h for 35 residents [43][44][45]. Data from three RACFs participating in the SIMPLER study suggests nurses spend an average of five minutes administering medications per resident per round [45].…”
Section: Clinical Significancementioning
confidence: 99%
“…Observational studies in Australian RAC homes have found that oral communication was the most frequent activity and the major communication channel between nursing staff, with residents and with outside service providers [2,[21][22][23]. About two-thirds of activities of nursing staff had a duration of 1 minute or less [2]; therefore nursing staff rarely had time to consult nursing records in the care delivery process [1]. Even in conducting high risk activity of medication management that requires clear information, the nursing staff only spent one to 2 minutes on reading residents' records in a threehour round [24].…”
Section: Lack Of Evidence Of Contribution Of Ehr To Risk Management Fmentioning
confidence: 99%
“…Residential aged care (RAC) services in Australia provide accommodation, meals, nursing and social care services for the frail older people by skilled and unskilled nursing staff [1,2]. Associated with the ageing process are increased levels of frailty and chronic diseases, which are the main challenges for nursing staff to provide appropriate and safe care [2].…”
Section: Introductionmentioning
confidence: 99%
“…Because the majority of residents are dependent on facility staff for medication administration [ 1 ], complex medication regimens are costly for aged care providers in terms of nursing time. A time–motion observational study of 12 morning medication rounds within one Australian residential aged care facility (RACF), involving seven nurses across two high care units, reported that nursing staff spent an average of three hours administering medications to 35 residents during the morning medication round [ 5 ]. Complex medication regimens can also be burdensome for residents, particularly for residents with dementia.…”
Section: Introductionmentioning
confidence: 99%